Permainan Ular Tangga Meningkatkan Pengetahuan dan Keterampilan Menyikat Gigi Anak Usia Dini - Muhammad Farhan Situmorang; Willia Novita Eka Rini; Puspita Sari; Asparian Asparian; Muhammad Rifqi Azhary (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Dental and oral health problems are still a major challenge for early childhood, especially due to the lack of knowledge and skills in brushing teeth properly. This study aims to determine the effect of the snakes and ladders game as an educational method in improving the knowledge and skills of brushing teeth of early childhood at Ar-Rahimah Kindergarten, Jambi City. This study used a quantitative method with a quasi-experimental one group pretest-posttest design. The research sample was 40 Ar-Rahimah Kindergarten students. The research instruments were knowledge questionnaires and skill observation sheets. The intervention given was a snakes and ladders game that had been modified with educational content related to dental health, accompanied by a demonstration using a tooth phantom. Analysis using the Wilcoxon Signed Ranks Test showed that there was a significant effect between before and after treatment on knowledge (p = 0.000) and skills (p = 0.000). The conclusion of this study is that the snakes and ladders game media can improve the knowledge and skills of brushing teeth of early childhood. It is recommended that the use of snakes and ladders game media can be used as an innovative approach in children's dental health education.